The impacts of mastectomy on life of women with breast cancer - Diego Augusto Lopes Oliveira; Laryanna Mayara de Lima Silva; Vitória Beatriz Nascimento de Souza; Vitória Luiza Rufino Bezerra; Nikaelle de Oliveira Cosme; Amanda Vasconcelos de Andrade Lima Silva (Universidade de Pernambuco, 2022)
Objective: Elucidate the impacts of mastectomy on the life of women with breast cancer. Methodology: Integrative review conducted in six stages in October and November 2020 guided by the PRISMA guide. The MEDLINE, BDENF, LILACS and Coleciona SUS databases were used as the search environment. Results: After the search process, 10 studies were identified that highlight the experience of discovering cancer, the feelings and impacts of mastectomy on the woman's daily life, and the importance of resignification for her new normal. Conclusion: The nursing care developed early and recognizing the woman's needs for coping with the consequences of the surgery is essential for reducing complications, empowering the woman, and improving her quality of life.